Hadron shower decomposition in the highly granular CALICE analogue hadron calorimeter. (23rd June 2016) - Eigen, G.; Price, T.; Watson, N. K.; Marshall, J. S.; Thomson, M. A.; Ward, D. R.; Benchekroun, D.; Hoummada, A.; Khoulaki, Y.; Apostolakis, J.; Dotti, A.; Folger, G.; et al.
Abstract: The spatial development of hadronic showers in the CALICE scintillator-steel analogue hadron calorimeter is studied using test beam data collected at CERN and FNAL for single positive pions and protons with initial momenta in the range of 10–80 GeV/ c . Both longitudinal and radial development of hadron showers are parametrised with two-component functions. The parametrisation is fit to test beam data and simulations using the QGSP_BERT and FTFP_BERT physics lists from GEANT4 version 9.6. The parameters extracted from data and simulated samples are compared for the two types of hadrons. The response to pions and the ratio of the non-electromagnetic to the electromagnetic calorimeter response, h / e, are estimated using the extrapolation and decomposition of the longitudinal profiles.